Peningkatan Efektivitas dan Tingkat Produksi terhadap Penggunaan Alat Pres serta Pengembangan Produk Inovatif dari Emping Melinjo - Ratu Sifa Ni’mah; Ulfi Jefri; Abdul Rohim; Heni Wahyuni; Nadya Mar’atul Rismayanti (Batara Wisnu : Indonesian Journal of Community Services, 2022)
Melinjo tree is a tree that is commonly found in Cilayang Village, Cikeusal District. Melinjo has many benefits, the wood can be used as a simple board and household appliance, the young leaves are referred to as so in Javanese used as vegetable ingredients, for example in the vegetable asem flowers and seeds that are still small or that have been cooked are also used as vegetables, melinjo seeds are also used as raw materials for emping, and the skin can be used as a vegetable. To improve the economy of the people of Cilayang Village, especially for housewives, it is necessary to have innovation from this melinjo. The implementation of this community service activity is in the form of assistance for EMPING MSMEs in Cilayang Village. The innovation carried out from emping is by creating a press machine to facilitate the production process, variations in emping flavors with four flavors, namely original, salty, pedaas, and original. As well as the packaging of empings that are packaged to be more modern.  As a result of this activity, the people of Cilayang Village are able to produce light food from melinjo fruit